Teacher Perspectives When Learning Trauma-Informed Practice Pedagogies: Stories of Meaning Making at Work - Brunzell, Tom; Waters, Lea; Stokes, Helen (Frontiers in Education, 2022)
This qualitative study focused upon ways teachers make meaning when working with students who are affected by trauma. An 11-month longitudinal design was used to explore teachers’ perspectives (N = 18 teachers) as they reflected upon the impacts of trauma within their classrooms and as they learned about trauma-informed practice strategies. Data from group interviews and participant journals was analysed using interpretative phenomenological analysis. Results emerged that suggested common pathways in the ways teacher perspectives evolved; and these pathways were then analysed in light of the meaningful work literatures to further suggest how work became more meaningful to these teachers when learning trauma-informed practice strategies. Teachers fostered a greater sense of meaning at work via two pathways: first by increasing their own wellbeing via personal use of trauma-informed strategies; then second, by incorporating trauma-informed strategies into their pedagogy to more effectively engage their students with learning. Increasing meaningful work for teachers who are working with trauma-affected students has promising implications for teacher professional development and workforce sustainability in schools experiencing high rates of teacher turnover and burnout as a result of teacher exposure to adverse student behaviour.